2016
DOI: 10.1152/ajpheart.00759.2015
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of mitochondria in neurons promotes activation of nitric oxide synthase and generation of nitric oxide

Abstract: -The diverse signaling events following mitochondrial depolarization in neurons are not clear. We examined for the first time the effects of mitochondrial depolarization on mitochondrial function, intracellular calcium, neuronal nitric oxide synthase (nNOS) activation, and nitric oxide (NO) production in cultured neurons and perivascular nerves. Cultured rat primary cortical neurons were studied on 7-10 days in vitro, and endothelium-denuded cerebral arteries of adult Sprague-Dawley rats were studied ex vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…10). In a recent study, we found that preconditioning with diazoxide protected cultured neurons against oxygen-glucose deprivation (OGD) via steps beginning with mitochondrial activation and involving production and generation of NO (50,89). We had previously shown that NO is also a major component in the induction of preconditioning in the intact brain following cortical spreading depression (75) and similar results have been reported by other laboratories (142).…”
Section: Role Of Mitochondria In Cellular Protectionsupporting
confidence: 66%
See 4 more Smart Citations
“…10). In a recent study, we found that preconditioning with diazoxide protected cultured neurons against oxygen-glucose deprivation (OGD) via steps beginning with mitochondrial activation and involving production and generation of NO (50,89). We had previously shown that NO is also a major component in the induction of preconditioning in the intact brain following cortical spreading depression (75) and similar results have been reported by other laboratories (142).…”
Section: Role Of Mitochondria In Cellular Protectionsupporting
confidence: 66%
“…Although it has been suggested that mitochondria contain a variant of nitric oxide synthase (NOS) in normal cells, and thus could produce NO via this enzymatic pathway, there is significant evidence against this view (98-100). Nonetheless, NO arising from nonmitochondrial sources, such as endothelial cells, VSM, astroglia, pericytes, and neurons (88,89) can affect the functioning of the electron transport chain by reducing mitochondrial oxygen consumption and ATP production (132) and could combine with superoxide anion to form peroxynitrite (54,58,145). We have shown that peroxynitrite is a potent activator of mitochondria (101).…”
Section: Mitochondrial Morphologymentioning
confidence: 88%
See 3 more Smart Citations